Bahram Gur bin Yazdegerd - Abbas, Mustafa (Kufa Journal of Arts, 2021)
The study of personalities is one of the studies that have a great impact on historical research, because of its importance in providing information that we do not find in general history narrations. There was a wide debate between the Arab and Persian sources, and both his virtues and virtues were disputed, so the features of his biography were double depicted between what the Arabs and the Persians saw, hence the reason for our choice of this topic, which extended from his birth to his death, and it relied on a group of primary sources and a number of secondary references